An Integrated Control Model (Chemical and Biological) via Fuzzy Linear Programming for Spodoptera frugiperda (Lepidoptera: Noctuidae) - Santos, P. N.; Peixoto, M. S.; Carvalho, S. M. S. (Trends in Computational and Applied Mathematics, 2024)
This paper proposes an integrated control model that enables the pesticide use according to the prey density and the insertion of the natural enemy, the predators, by fuzzy linear programming. The fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) is one of the main resistant pests of corn, which can cause damage to the productivity up to 34%. The control is strictly chemical.